Social Mobility in Post-socialist Countries: State of the Art and Topical Research Issues - Tatarėlienė, Dovilė (Sociologija. Mintis ir veiksmas, 2017)
The purpose of this article is to provide an analytical review of the research of social mobility in post-socialist countries. The first section introduces the concept of social mobility and describes certain social mobility measurement techniques based on different models of social structure. In the second section of the article, we outline the features of social mobility research pertaining to the socialist period. Further, social mobility studies are grouped according to an application of different social structure models into class and non-class (status attainment) approaches. The third part of the article analyses the inter-class social mobility studies, with an emphasis on class schemes applied and the distinction between absolute and relative social mobility. The fourth section presents the research, relying on the status attainment model, highlighting the characteristic features and limitations of this methodology of the research on social mobility. In the fifth part of the article, we discuss the less common type of social mobility studies – subjective social mobility research. The final section provides an overview of social mobility research in Lithuania, discussing the social mobility studies both in socialist and post-socialist Lithuania.